USING ERROR FEEDBACK TO IMPROVE STUDENTS’ WRITING SKILL OF THE SEVENTH GRADE STUDENTS - Windarti Dian Ekowati Kusumaningrum (Universitas Sarjanawiyata Tamansiswa, 2018)
The research aims to (1) describe the implementation and (2) find out the results of using error feedback to improve students’ writing skill of the seventh grade students at SMP N 3 Berbah Sleman. This action research conducted in two cycles which the subject was the students of VII D of SMP N 3 Berbah Sleman consisting of thirty-one students. To collect the data,the writer conducted the observation and interview. The qualitative data were obtained through observation and interviews. The results show that (1) the implementation of error feedback in improving writing skill covers pre-writing, writing the product, feedback giving, revising the product, and writing the final product. (2)The result of using error feedback in improving writing skill is the students became more interested and enthusiastic in learning writing descriptive text.The students’ interest was increased.